Torque analysis of permanent magnet flux switching machines with rotor step skewing - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Shen, Jian-Xin (IEEE, 2012)
This paper investigates the torque characteristics of permanent magnet flux switching (PMFS) machines with rotor step skewing. The cogging torque, torque ripple and average output torque of a PMFS machine with a common stator and different rotor pole widths and rotor pole numbers are first established using two-dimensional (2-D) finite element analysis (FEA). A cost-effective rotor step skewing technique is then proposed to reduce the cogging torque and torque ripple of the machine with two different rotors. The results have revealed that the least step number and angle for optimal torque ripple mitigation of the PMFS machine are determined by the harmonic contents of the torque pulsation and the rotor pole number. The influences of load conditions on the machine torque characteristics are carried out by varying current excitations. The corresponding three-dimensional (3-D) FEA models are constructed and experimental prototypes are built for validations.